Cation-directed atropselective synthesis of BINOL derivatives - Jolliffe, JD (2017)
The use of chiral counterions to facilitate enantioselective mono-C-alkylation of enolates has been explored extensively over the past century. We have demonstrated that an alternative mode of reactivity – O-alkylation – predominates if the C-alkylation is impeded. We have applied this concept to the atropselective dynamic kinetic resolution of 1-aryl-2-tetralones, leading to an organocatalytic synthesis of enantio-enriched BINOL derivatives. In this reaction, the chiral counterion plays a key role as both a phase-transfer catalyst and also as the agent to facilitate atropselective alkylation of rapidly interconverting axially chiral enolates. Treatment of 2-tetralones with base in the presence of an ammonium salt leads to intermediate atropisomeric dihydro-BINOL; oxidation with DDQ leads to BINOLs without loss of e.r. This transformation leads to high enantioselectivity and the scope of this reaction is significant: we can insert substituents into any position around the BINOL core, and we can also generate heavily functionalized derivatives without compromising stereochemical integrity. By employing a substoichiometric amount of alkylating agent, we have applied our reaction protocol to the kinetic resolution of MeBINOL with good selectivity.